One number is 3 less than twice another. If their sum is 39, find the numbers.
Which of the following systems of equations represents the word problem?
y = 2x - 3 and y = x + 39
y = 2x - 3 and x + y = 39
y = 2(x - 3) and x + y = 39

Question

Asked 9/18/2014 8:03:12 AM

Updated 9/18/2014 8:28:51 PM

4 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by yeswey [9/18/2014 8:27:21 PM]

s

cutyglyde|Points 461|

andrewpallarca|Points 42851|

Question

Asked 9/18/2014 8:03:12 AM

Updated 9/18/2014 8:28:51 PM

4 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by yeswey [9/18/2014 8:27:21 PM]

Rating

8

The euqation of the line that passes through (-1, -3) and (2, 1) in standard form is 4x - 3y = 5

Added 9/18/2014 8:23:30 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [9/19/2014 2:17:58 AM]

8

The equation of the line that passes through (1, 5) and (-2, 3) in standard form is 2x - 3y = -13

Added 9/18/2014 8:26:42 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [9/19/2014 2:18:28 AM]

8

5x + 10y = 18, x = y - 6 The result of substituting y - 6 in for x in the first equation is: 5y - 30 + 10y = 18

Added 9/18/2014 8:28:51 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [9/19/2014 2:18:45 AM]

Divide the following polynomials, then place the answer in the proper location on the grid. Write answer in descending powers of x.
(27x^4 - 18x^3 + 9x^2) ÷ 3x

Question

Updated 9/12/2014 11:15:06 AM

1 Answer/Comment

(27x^4 - 18x^3 + 9x^2) ÷ 3x

= (27x^4/3x) - (18x^3/3x) + (9x^2/3x)

= 9x^3 - 6x^2 + 3x

= (27x^4/3x) - (18x^3/3x) + (9x^2/3x)

= 9x^3 - 6x^2 + 3x

Added 9/12/2014 11:15:06 AM

This answer has been confirmed as correct and helpful.

Divide the following polynomials, then place the answer in the proper location on the grid. Write answer in descending powers of x.
(12x3 - 11x2 + 22x - 5) (4x -1)

Question

Updated 9/12/2014 11:13:46 AM

1 Answer/Comment

(12x^3 - 11x^2 + 22x - 5) ÷ (4x - 1)

= (12x^3/4x - 1) - (11x^2/4x - 1) + (22x/4x - 1) - (5/4x - 1)

= 3x^2 - 2x + 5

= (12x^3/4x - 1) - (11x^2/4x - 1) + (22x/4x - 1) - (5/4x - 1)

= 3x^2 - 2x + 5

Added 9/12/2014 11:13:46 AM

This answer has been confirmed as correct and helpful.

Evaluate |-10| - |-8|
-2
2
18

Question

Updated 9/11/2014 9:28:11 AM

1 Answer/Comment

|-10| - |-8| = 10 - 8 = 2

Added 9/11/2014 9:28:11 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [9/11/2014 9:31:53 AM]

Factor completely, then place the answer in the proper location on the grid.
12a^2 - 36ab + 27b^2
**Weegy:** 12a^2 - 36ab + 27b^2 = 3(2a - 3b)^2 **User:** Subtract the following polynomials, then place the answer in the proper location on the grid. Write the answer in descending powers of a.
Subtract: 16a 2 - 32a + 9 from 12a 2 + 60a - 8. **User:** Multiply the following polynomials, then place the answer in the proper location on the grid. Write the answer in descending powers of x.
(8x + 3)(4x + 7)
**Weegy:** (8x + 3)(4x + 7) = 32x^2 + 12x + 56x + 21 = 32x^2 + 68x + 21 **User:** Divide the following polynomials, then place the answer in the proper location on the grid. Write the answer in descending powers of a.
Divide 5a^2 + 6a - 9 into 25a^4 + 19a^2 - a - 78. (More)

Question

Not Answered

Updated 9/12/2014 7:54:22 AM

1 Answer/Comment

(12a^2 + 60a - 8) - (16a^2 - 32a + 9)

= (12a^2 + 60a - 8) + (-16a^2 + 32a - 9)

= -4a^2 + 92a - 17

= (12a^2 + 60a - 8) + (-16a^2 + 32a - 9)

= -4a^2 + 92a - 17

Added 9/12/2014 7:54:22 AM

This answer has been confirmed as correct and helpful.

Factor completely, then place the answer in the proper location on the grid.
16x4 - 64y8

Question

Updated 9/12/2014 8:26:28 AM

1 Answer/Comment

16x^4 - 64y^8 = 16(x^4 - 4y^8) = 16(x^2 - 2y^4)(x^2 + 2y^4)

Added 9/12/2014 8:26:28 AM

This answer has been confirmed as correct and helpful.

32,488,452

questions answered

There are no comments.